Using behaviour science to enrich development: understanding attitudes related to behavioural change and environmental management in low-resource communities. Issue 7 (3rd October 2022) - Simmons, Erik; Pickering, John; Sanders, Matthew
ABSTRACT: Low-resource communities that rely on the environment face challenges in the forms of climate change and the overuse of natural resources. Behaviour science offers methods and strategies to mitigate behaviours that contribute to environmental degradation, as well as promote the adoption of desirable behaviours. We investigated the attitudes and beliefs of vulnerable communities. We conducted surveys across five villages on Selayar Island, a small island in Sulawesi Indonesia. Our results suggest a willingness to participate in behaviour-based programs and concern for families. When offering development programs to communities, the needs of the community should inform the design and implementation process.